STRATEGI SUKSES MENINGKATKAN KINERJA GURU SENIOR UNTUK MUTU PENDIDIKAN YANG UNGGUL DI SEKOLAH MENENGAH - Nurfaisal Nurfaisal; Sunengko Sunengko; Ali Asfar (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2023)
The research examines the optimization of senior teachers’ performance in order to enhance the quality of education in secondary schools. Senior teachers’ refer to those who are above the age of fifty and possess extensive experience in the field of education. They may even serve as subject intructors or former subject instructor. They reality on the ground is that their potential is often overlooked by the school prinsipals and their capabilities remain untapped. Furthermore, three is tendency to label them as old, locking energy, and no longer possessing potential. Based on the aothor’s experience as asecondary school principal, it is evident that the author consistenly atilizes the knowledge and experience of senior teachers to great effect, incorporating them as part of a team to improve the school’s quality. This is because they not only possess mastery over instructional strategies but also have considerable experience in montoring junior teachers. Moreover, considering the presence of numerouse new teachers in schools who require guidance and mentorship to become professional educators, the school principals should leverage the knowledge and experience of senior teachers to enhance the educational quality within the school. The principal should estabilish methods to optimize the performance of these senior teacher, and it is these approaches and strategies that the author will discuss in this article.